Impact of COVID-19 on environmental services workers in healthcare settings: a scoping review. (December 2022) - Ng, Q.X.; Yau, C.E.; Yaow, C.Y.L.; Lim, Y.L.; Xin, X.; Thumboo, J.; Fong, K.Y.
Summary: Background: In the wake of the coronavirus disease 2019 (COVID-19) pandemic, demand for deep cleaning and environmental services workers grew exponentially. Although there is extant literature examining the impact of the COVID-19 pandemic on healthcare workers, less emphasis has been placed on environmental services workers, who play an equally important front-line role. Aim: To examine the impact of the COVID-19 pandemic on environmental services workers employed in healthcare settings. Methods: Scoping review methodology. A search strategy was developed, in consultation with a medical information specialist, employing various combinations of the keywords [(environmental services worker OR health attendant OR housekeeping) AND (COVID OR coronavirus OR pandemic OR epidemic)]. Four bibliographical databases were searched from inception to 5 th July 2022: OVID Medline, Embase, Cumulative Index to Nursing and Allied Health Literature (CINAHL) and Cochrane Database. Results: In total, 24 studies were included in this review. The studies were generally cross-sectional in design. Seroprevalence studies highlighted significantly higher rates of COVID-19 among environmental services workers (housekeeping, cleaning and janitorial staff) compared with other clinical and non-clinical staff in the same institutions. In addition, based on qualitative interviews, environmental services workers experienced greater psychological stress working during the pandemic. Conclusions: Environmental services workers were particularly vulnerable to increased work stress and COVID-19 during the pandemic. Health systems need to do more to support these workers. Further research could investigate specific policy and procedural changes to benefit this under-recognized group in the greater healthcare workforce.